Micro-bionic : radical electronic music and sound art in the 21ste century - Bey, Thomas; Bailey, William ([London] : Creation Books, 2009)
Resistance of the cell : industrial music vs. the "control machine" -- Libertines or asceticists? : a quarter-century of Whitehouse -- Re-launching the dream weapon : an unnatural histury of Coil -- Electrovegetarianism : an abridged history of Merzbow, from biomechanic to biophiliac -- Mash communication (and other symptoms of the sampling virus) -- Beyond the valley of the falsch : Mego (and friends) revitalize "computer music" -- To kick a king : the Kingdoms of Elgaland and Vargaland -- Francisco López : the big blur theory -- Vox stimuli : John Duncan's unrestrained explorations -- Uncommon sense(s) : synesthesia and electronic music -- Silence is sexy : the other "extreme" music -- Faster than light (and cheaper) : the great immaterial music debate -- Technomadism : taking electronic music beyond the mass media centers. [CD] Get out 2 / Pita (2:08) -- Fa / Fennesz (4:36) -- Beneath my sun-proof eyelids, truth never sleeps / COH (8:02) -- Zes / GOEM (3:55) -- Punani 7 excerpt / EVOL (3:26) -- Crowd pleaser : alternate mix / Consumer Electronics (3:16) -- The north is protected / Leif Elggren (11:29) -- 60 La Scala / Scott Arford (5:00) -- Tap internal : excerpt / John Duncan (8:51) -- Anicca part 3 : extract / Merzbow (11:37) -- Untitled #151 / Francisco López (4:11). Andere titels: MicroBionic
boek